A comparative study on the machinability of Ti-6Al-4V using conventional flood coolant and sustainable dry machining. (2015) - Dawood, Abdulhameed; Arbuckle, Gregory K.; Jahan, Muhammad P.
This study aims to conduct a comparative experimental investigation on the machinability of Ti-6Al-4V for conventional flood coolant machining and sustainable dry machining. The effect of cutting speed, feed rate and depth of cut on machining performance has been evaluated for both conditions. A comparative investigation on the tool wear mechanism and chip morphology for dry and wet machining has also been presented. The machining time and surface roughness were found to be lower in dry machining compared to wet machining. The tool wear was found to be unpredictable with no significant difference for dry and wet machining, although cutting tools suffered from more adhesion of chips during dry machining. The flank wear and chipping were more common in wet machining, whereas crater wear and build-up edge were predominant in dry machining. Comparing all the parameters, sustainable dry machining was found to provide better performance for machining Ti-6Al-4V.